PHYSICAL THERAPY FOR METABOLIC SYNDROME (LITERATURE REVIEW) (Physical Culture and Sport: Scientific Perspective, 2025)
Metabolic syndrome is a cluster of conditions that occur together, increasing the risk of developing coronary heart disease, stroke, and type 2 diabetes. Metabolic syndrome is observed in approximately 25% of all adults, with prevalence increasing with age. The presence of any one component of metabolic syndrome increases the risk of developing metabolic syndrome later in life and represents a high risk of cardiovascular disease throughout life. Metabolic syndrome now affects 30–40% of people under the age of 65, mainly due to weight gain in adulthood and a genetic or epigenetic predisposition to abdominal fat/ectopic fat accumulation associated with poor intrauterine development. The article presents a generalized review of current scientific sources devoted to the role of physical therapy in a comprehensive approach to the treatment and prevention of metabolic syndrome. The effect of various types of physical activity on the main components of the metabolic syndrome is analyzed: insulin resistance, abdominal obesity, arterial hypertension, and others. It is demonstrated that systematic physical activity contributes to weight loss, improvement of insulin sensitivity, normalization of blood pressure and lipid profile. The mechanisms of action of physical activity on the body's metabolic processes are highlighted, in particular, increasing insulin sensitivity, normalization of lipid profile and reduction of systemic inflammation. The recommendations of international clinical guidelines on the dosage of physical activity and their combination with other components of non-drug therapy are considered. Data on the effectiveness of individualized physical therapy programs depending on age, level of physical fitness and concomitant pathology are summarized. It is concluded that physical therapy has the potential not only to reduce the risks associated with metabolic diseases, but also to reduce the burden on the healthcare system, improving the quality of life of patients. In some individuals, an exercise program has been shown to improve risk markers to the point where they no longer meet the criteria for metabolic syndrome. The effectiveness of such interventions is explained by a complex of physiological, behavioral, and genetic factors. In particular, physical activity affects insulin sensitivity, fat metabolism, levels of systemic inflammation, and even epigenetic mechanisms of metabolic regulation.
Keywords: metabolic syndrome; physical therapy; abdominal obesity; non-drug treatment